New formulation calcium-based 45S5 bioactive glass: in vitro assessment in PBS solution for potential dental applications - Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Awang Kechik, Mohd Mustafa; Fen, Yap Wing; Amin, Khamirul Matori; Cheong, Wei Mun (Elsevier, 2023)
In this work, the designed bioactive glass utilized waste is expected to improve mechanical properties while maintaining the bioactivity performance during the in-vitro assessment. Herein, the novel bioactive glasses were prepared using the melt-quenching approach. Phosphate buffer saline was used as an immersion medium during the in-vitro bioactivity and biodegradability evaluation to ascertain the glass's bioactivity characteristics. The XRD results indicated the carbonate apatite phase for sample 0F and the fluorapatite and calcite phase for sample 3F, supported by the FTIR spectra. Further, the pH increased from (7.437 ± 0.004) to (9.699 ± 0.058) for 0F and (9.635 ± 0.014) for 3F, indicating the samples' bioactivity in response to the immersion medium. In addition, 3F exhibited a higher hardness (3.29 ± 0.07 GPa) and toughness (2.4 ± 0.08 MPa m1/2), supported by the weight gained in the biodegradability analysis. This work offers a promising technique to fabricate the bioactive glass incorporating waste, adding fluoride content into the glass for potential dental application.